Cultural Factors that Support Community Participation in Village Development - Halid Hasan; Farika Nikmah; Siti Nurbaya; Sudarmiatin Sudarmiatin (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
Society culture is an inherent tradition and guides the good and bad of every resident's action and behaviour. Society culture is synonymous with ancestral heritage. In this study, the culture defined consisting of involvement, consistency, adaptability, and mission that carried out and performed by village government, so as to stimulate residents' intentions to participate in village development. The research used a quantitative approach, with the population of   residents of the village of Krebet, Malang Regency. Data obtained by distributing questionnaires to residents. 130 questionnaires returned and declared appropriate so that this number was used as the research sample. Data were analyzed statistically by Minitab. The independent variables in this study are culture factors, namely involvement, consistence, adaptability and mission and the dependent variable is society participation in village development. The results of the study found that there was a partially positive and strong relationship between the independent variables and the dependent variable. Culture contributed 70% to society participation. Additionally, consistency was the strongest influencer followed by involvement, adaptability and lastly mission. Moreover, the results of this study provide evidence that when there is a good way from the village goverment in managing the culture in the form of tradition in the society, the greater the society's intention to participate in the village development.